Internet usage among agro-based entrepreneur: can it affect productivity? - Hassan, Md. Salleh; Mohamed Shaffril, Hayrol Azril (Friends Science Publishers, 2009)
This study was conducted to evaluate the impact of internet usage on agro-business productivity and factors affecting it. A total of 164 respondents were involved in the study representing agro-based entrepreneurs in Peninsular Malaysia. The respondents involved in agro-business such as food processing, plantation, animal rearing, farming, fisheries and non-food processing. Respondents were chosen based on the list of agro-based entrepreneurs provided by the Department of Agriculture (DOA), Farmers Organization Authority (FOA) and Agriculture Bank of Malaysia. A survey using a questionnaire developed for the study was used to collect data. Mean, percentage, frequency and independent t-test were generated to describe the general trend of the data. From the results obtained, the level of internet applications usage was at moderate level, while all of the eight internet applications listed in the study showed significant difference in term of internet potential contribution to agro-based productivity comparing between the users and non-users of the listed internet applications.